Interactome-based approaches to human disease. Issue 3 (June 2017) - Caldera, Michael; Buphamalai, Pisanu; Müller, Felix; Menche, Jörg
Abstract: Recent advances in high-throughput technologies have created exciting opportunities for systematically investigating the molecular basis of human disease. In addition to a growing catalog of disease-associated genetic variations, we can now map out an increasingly detailed network diagram of the complex machinery of interacting molecules that constitutes the basis of (patho-) physiological states. The emerging field of 'network medicine' applies tools and concepts from network theory to interpret this diagram and elucidate the relation between perturbations on the molecular level and phenotypic disease manifestations. The interactome, i.e. the integrated network of all physical interactions within the cell, can be interpreted as a map and diseases as local perturbations. Network-based approaches can aid in identifying the specific interactome neighborhood that is perturbed in a certain disease, guide the search for therapeutic targets and reveal common molecular mechanisms between seemingly unrelated diseases. Graphical abstract: Highlights: The interactome represents a network of all molecular interactions in the cell. Interactome structure and biological function are intimately connected. Disease associated genes aggregate in local interactome neighborhoods. Network-based algorithms can help elucidate the molecular mechanisms of diseases.